SARS-CoV-2 and self-medication in Cameroon: a mathematical model. (1st January 2021) - Kong, Jude D.; Tchuendom, Rinel F.; Adeleye, Samuel A.; David, Jummy F.; Admasu, Fikreab Solomon; Bakare, Emmanuel A.; Siewe, Nourridine
ABSTRACT: Self-medication is an important initial response to illness in Africa. This mode of medication is often done with the help of African traditional medicines. Because of the misconception that African traditional medicines can cure/prevent all diseases, some Africans may opt for COVID-19 prevention and management by self-medicating. Thus to efficiently predict the dynamics of COVID-19 in Africa, the role of the self-medicated population needs to be taken into account. In this paper, we formulate and analyse a mathematical model for the dynamics of COVID-19 in Cameroon. The model is represented by a system of compartmental age-structured ODEs that takes into account the self-medicated population and subdivides the human population into two age classes relative to their current immune system strength. We use our model to propose policy measures that could be implemented in the course of an epidemic in order to better handle cases of self-medication.